Pelatihan Sertifikasi Halal sebagai Strategi Membangun Kepercayaan Konsumen bagi Masyarakat Desa Gadingkulon, Kecamatan Dau, Kabupaten Malang - Esy Nur Aisyah; Maretha Ika Prajawati; Didik Wahyudi (IKIP PGRI Bojonegoro, 2020)
This activity is motivated by the products of the Gadingkulon villagers who have low bargaining power, their lack of ability in packaging and selling products is also an obstacle. Besides, many business actors have not pocketed and are not sufficiently knowledgeable about halal certification from MUI for the products they produce, so they will find it difficult to market their products to souvenir centers, supermarkets, and other markets. Guaranteed halal products through halal product certificates will provide comfort, safety, safety, and certainty of the availability of halal products for people in consuming and using halal products and can increase added value for business actors to produce and sell halal products. Therefore, they need to be equipped with knowledge and training on halal certification steaming. This service activity consists of 4 stages, namely preparation, meeting, training, and monitoring and evaluation. The community service activities carried out in Gading Kulon Village, Dau District, Malang Regency are going well. The result of community service activities is that people who have joint products with the Halal Center of UIN Maulana Malik Ibrahim Malang help meet and identify all the requirements needed and will then be bridged by the Halal Center of UIN Maulana Malik Ibrahim Malang until the issuance of halal certificates.